2014
DOI: 10.4238/2014.february.21.5
|View full text |Cite
|
Sign up to set email alerts
|

cDNA-AFLP transcriptional profiling reveals genes expressed during flower development in Oncidium Milliongolds

Abstract: ABSTRACT. The flower developmental process, which is crucial to the whole lifecycle of higher plants, is influenced by both environmental and endogenous factors. The genus Oncidium is commercially important for cut flower and houseplant industry and is ideal for flower development studies. Using cDNA-amplified restriction fragment length polymorphism analysis, we profiled transcripts that are differentially expressed during flower development of Oncidium Milliongolds. A total of 15,960 transcript-derived fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Large numbers of TDFs were differentially expressed in different developmental stages or diverse conditions, which were involved in various biological processes (Gupta et al, 2012 ). In this study, 328 TDFs were identified by differential expression in the early seedling stage under salt stress, and the GO enrichment and KEGG analysis showed that most of the TDFs were predominantly involved in transport, transcription, translation, carbohydrate transport, metabolism, protein synthesis, and protein fate ( Figure 12 ), which are consistent with those found in Oncidium milliongolds and Lavandula angustifolia (Qian et al, 2014 ; Banikamali et al, 2020 ). It has been reported that genes involved in metabolism and energy are activated early in seedlings and persist in functioning during growth (Guo et al, 2009 ).…”
Section: Discussionsupporting
confidence: 79%
“…Large numbers of TDFs were differentially expressed in different developmental stages or diverse conditions, which were involved in various biological processes (Gupta et al, 2012 ). In this study, 328 TDFs were identified by differential expression in the early seedling stage under salt stress, and the GO enrichment and KEGG analysis showed that most of the TDFs were predominantly involved in transport, transcription, translation, carbohydrate transport, metabolism, protein synthesis, and protein fate ( Figure 12 ), which are consistent with those found in Oncidium milliongolds and Lavandula angustifolia (Qian et al, 2014 ; Banikamali et al, 2020 ). It has been reported that genes involved in metabolism and energy are activated early in seedlings and persist in functioning during growth (Guo et al, 2009 ).…”
Section: Discussionsupporting
confidence: 79%